Dietary Approaches in Managing Obesity - Jayawardena, Ranil (Faculty of Medicine, University of Colombo, 2020)
The recent surge in rates of obesity is driven by eating behaviours and food choices that promote excessive energy intake. Reducing caloric intake ...
Keywords: Obesity